Professional Activities of Disabled People as a Factor of the Development of Education in an Inclusive Society - M. E. Kudryavtseva; S. S. Lebedeva (Дискурс, 2022)
Introduction. The article deals with the problem of professional activity and education of persons with disabilities. The implementation of the ideas of inclusive education could be successful if the experience of persons with disabilities who have productively built their professional trajectory and actively participate in public, educational, sociocultural and other initiatives of modern society is taken into account.Methodology and sources. The problem of professional and creative realization of people with disabilities is considered in line with the socio-educational approach, which implies the need to integrate people with disabilities into all spheres of modern society, as well as in line with the environmental approach, which involves considering the problem of the quality of life of people with disabilities. The article is based on the articles of such authors as O.S. Andreeva, A.V. Gruzintsev, M.A. Dymochka, A.A. Kirillovykh, S.N. Kashtanova, V.A. Kudryavtsev, S.S. Lebedeva, N.T. Selezneva, A.V. Cherdakova, as well as materials of 25 scientific and practical conferences (1994–2020). The article uses methods of content analysis of an array of 1553 articles based on conference materials, as well as the case study method.Results and discussion. In the process of evaluating the array of publications, the authors concluded that persons with disabilities actively participating in professional activities and social work reflected many aspects of the problem of inclusive education. Theoretical and practical conclusions and examples given in the case study showed that the experience of people with disabilities working in the socio-cultural and educational fields, who develop the inclusive capabilities of people with disabilities with the help of advanced digital technologies, seems to be especially successful. An analysis of the professional activities of persons with disabilities led to the conclusion that its meaning and essence are associated with the formation of an inclusive society.Conclusion. The authors conclude that people with disabilities are the initiators and organizers of relevant areas of activity that contribute to the active support of people with disabilities in the process of their lifelong education.